The predictive validity of common entrance examination and students’ academic performance into Secondary Schools in Bamenda III Subdivision - Kibinkiri Eric Len; Ngeloh Margaret (International Journal on Integrated Education, 2021)
This study set out to ascertain the extent to which the grade scored in Common Entrance (CE) predicts students’ Academic performance into Secondary Schools (especially Form One) in Bamenda III Subdivision. The sample used for this study was 190 Form One (1) students from Two (2) Government Secondary Schools, One (1) private school and One (1) mission Secondary School in Bamenda III subdivision. Data collection was done through personal administration of questionnaires to students. The data was collected from selected Secondary Schools and from the Regional Delegation of Basic Education. The statistical methods used were descriptive and inferential statistics. The hypotheses were tested at a0.05 level of significance. The Pearson Product Moment Correlation and SPSS version 2.0 were used to analyse data. Findings showed that there was a weak negative correlation coefficient (-0.009) between total CE score and Term One (1) score in English Language with an alpha value of 0.907 which is non-significant (hypothesis 1). Findings on hypothesis 2 showed that there was a weak correlation coefficient (-0.066) between CE English Language score and Term One (1) score in English Language with an alpha value of 0.365 which is non-significant. Also the findings on hypothesis 3 showed that there was a weak correlation coefficient (0.059) between CE Mathematics score and Term One (1) score in Mathematics with an alpha value of 0.419 which is non-significant. This study therefore concludes that CE does not significantly predict students’ academic performance into Secondary schools. The study recommends that, CE results to an extent should not be used as the only criteria for selection and placement of students in Secondary Schools in Cameroon